Benang yang Hilang: Mengurai Alienasi Kultural Hindu dan Aniaya Budaya di Tengah Urbanisasi Generasi Z - Sumertini, Ni Wayan (Kamaya: Jurnal Ilmu Agama, 2024)
Cultural alienation has resulted in changes in the religious culture and feelings of generation Z with several cultural cases causing a sharp decline in cultural values, customs and religious practices. This is especially sad in the context of Hinduism, where traditional traditions are at risk of extinction, as a result of cultural persecution and cultural alienation. The aim of this research is to reveal the extent of the cultural transformation experienced by Generation Z during the urbanization process, as well as identify specific factors that contribute to cultural alienation and persecution within the Hindu community by proposing effective solutions and interventions to mitigate the decline in cultural values, customs, and Hindu religion. Researchers use qualitative research with the research approach that will be used is ethnography. Data collection techniques using in-depth interviews, surveys and participant observation. In a novel way, this research introduces a new perspective by focusing on the intersection between urbanization, Generation Z, and Hindu culture, revealing the intricacies of cultural alienation and cultural persecution. The results of this research show that traditional customs are giving way to a more contemporary lifestyle, which shows that there is a complex negotiation between cultural heritage and modernity, so that factors emerge that contribute to cultural alienation, including (1). Peer influence, (2). The impact of media hegemony (flexing content) and the rapid pace of urban life emerge as the main factors contributing to cultural alienation among Generation Z. Several solutions to increase the fighting power of Generation Z return to the axis of Hindu culture and religion, without abandoning the positive innovations of the impact of urbanization, including: (1) Strengthening Cultural Education, (2) Community Engagement Initiatives, (3) Adapting Traditions in a Modern Context, (4) Digital Platforms for Cultural Awareness, (5) Intergenerational Cross Experience. It is concluded that the cultural structure of Generation Z in a dynamic urbanization landscape requires special handling and that preserving values and traditions is a shared responsibility for all aspects of social life.